2002
DOI: 10.1097/00126334-200212150-00008
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection in Rural Villages of Cameroon

Abstract: We have documented a wide range of HIV prevalences among rural villages of Cameroon. Age, marital status (in women) and sexual risk factors appear to be associated with HIV infection in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…Population-based surveys of HIV infection prevalence among older adults would provide more reliable and robust data. 29 and a study among people admitted to hospital in Dar es Salaam, United Republic of Tanzania, reported a prevalence of 15% among those aged ≥ 55. 30 A study in the Congo described 175 cases of HIV infection among people aged ≥ 55 years from 1990 to 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based surveys of HIV infection prevalence among older adults would provide more reliable and robust data. 29 and a study among people admitted to hospital in Dar es Salaam, United Republic of Tanzania, reported a prevalence of 15% among those aged ≥ 55. 30 A study in the Congo described 175 cases of HIV infection among people aged ≥ 55 years from 1990 to 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that urban residents, and particularly urban youth, tend to show higher levels of awareness of HIV/AIDS and ways of avoiding HIV infection than rural residents [16], but are more prone to risky sexual behaviour. Studies in Cameroon have shown that poor single mothers, spinsters or unemployed migrants from rural to urban areas, uneducated girls, and petit traders involved in bar business engage in sexual relations to meet with up with their basic economic needs and take care of their children [25]. For this group, assistance with economic survival; (fees to stay in school, living expenses, food and cloth are their motivations for entering high risky and unprotected sexual relationship [14,25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Cameroon have shown that poor single mothers, spinsters or unemployed migrants from rural to urban areas, uneducated girls, and petit traders involved in bar business engage in sexual relations to meet with up with their basic economic needs and take care of their children [25]. For this group, assistance with economic survival; (fees to stay in school, living expenses, food and cloth are their motivations for entering high risky and unprotected sexual relationship [14,25]. Recent studies using UNAIDS data have shown that, in many countries of SSA, HIV/AIDS is disproportionately an urban phenomenon [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such recombinant, CRF02_AG, is prevalent in West-Central Africa, playing a significant role in the epidemic [Montavon et al, 2000;Carr et al, 2001;Nyambi et al, 2002a;Burda et al, 2004]. CRF02_AG accounts for greater than 65% of infections in Cameroon, cocirculating among a broad genetic diversity of HIV-1 strains, including all groups, all group M (sub-)subtypes, and a vast array of recombinants [Zhong et al, 2002[Zhong et al, , 2003Nyambi et al, 2002b]. Importantly, recent work showed that almost half of all URFs in the eastern parts of Cameroon contain genetic material of CRF02_AG [Konings et al, 2006b].…”
Section: Introductionmentioning
confidence: 99%